The role of tryptase in the human body: From normal to pathology - Zofia Lisiecka, Maria (Medicinski časopis, 2025)
The purpose of the work was to investigate the effect of the tryptase enzyme on the functioning of the human body in normal and pathological conditions. A search for relevant studies in the PubMed, Scopus, GoogleScholar, ResearchGate and Web of Science databases, presented for 2014-2024, was performed. The study revealed that tryptase is an enzyme of mast cells and a marker for assessing their activity. Tryptase is involved in the regulation of the growth and development of mesenchymal cells, fibroblasts and endothelial cells, regulation of blood clotting, metabolic processes of connective tissue, and affects the contractility of smooth muscle cells. Under pathological conditions, impaired tryptase metabolism leads to excessive fibrosis, development of keloid scars, narrowing of kidney vessels, transplant rejection, development of inflammatory bowel disease, arthritis, psoriasis, atopic and contact dermatitis. The normal level of serum tryptase is 5 ng/ml. The threshold value of the enzyme is 11.4 ng/ml. Increased levels of this enzyme are found in 4-6% of the population. An increase in serum tryptase levels is diagnosed in hereditary pathologies (hereditary alpha-tryptasemia) and acquired diseases (mastocytosis, mast cell activation syndromes, monoclonal mast cell activation syndrome, anaphylaxis, chronic kidney disease). The clinical picture is characterized by lesions of the cardiovascular, gastrointestinal, respiratory, excretory, and integumentary systems and the development of anaphylaxis. The pathogenesis of the diseases is still under investigation, so the treatment of the described pathologies is mainly symptomatic. It is concluded that tryptase is the main biomarker of mast cell function, and that impaired metabolism of this enzyme leads to a number of severe, life-threatening pathologies.